Program Akselarasi Sekolah - Fitri Sukmawati (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Government through the Ministry of National Education has accommodated the implementation of an accelerated program in anticipation of and maximizes the potential of students with ability above the average. Differentiated educational services by using a diversified curriculum can be implemented through the organization of the class acceleration system, so that children can develop the potential he/she has. Key words: Acceleration of school